Las herramientas tecnológicas e internet: influencia en las actividades comunicacionales de las empresas. - Araujo Apolo, Edison Enrique (My University, 2020)
Technological tools and the internet are considered key elements for the development of organizations, they are used in different areas and activities, one of them are communication activities which facilitate the management of adequate information throughout the company. In this sense, an analysis of the technological resources and tools of the internet in the organizational communication was carried out, to determine which of these are necessary in the optimization of business processes, by means of a methodology of documentary and descriptive character a bibliographic review and a analysis of the information collected, which allowed identifying the different technological tools and internet capacity that a company in the industrial sector has; As a result, a table was developed that allowed clarifying the resources that the company usually uses to communicate with customers and suppliers, among them web portals, social networks (WhatsApp, Facebook, Instagram and Twitter) and mobile telephony, considering them acceptable, but not necessarily optimal when establishing adequate communication. It is concluded, then, that to facilitate communication with customers and suppliers, it is necessary to implement tools aimed at providing competitive advantages, and that they are combined with the resources available to the organization, in order to improve business functionality.
Las herramientas tecnológicas y el internet son considerados elementos claves para el desarrollo de las organizaciones, son utilizadas en distintas áreas y actividades, una de ellas son las actividades de comunicación las cuales facilitan el manejo de información adecuada en toda la empresa. En este sentido, se realizó un análisis de los recursos tecnológicos y herramientas del internet en la comunicación organizacional, para determinar cuál de estas son necesarias en la optimización de procesos empresariales, mediante una metodología de carácter documental y descriptiva se realizó una revisión bibliográfica y un análisis de la información recopilada, la cual permitió identificar las diferentes herramientas tecnológicas y capacidad de internet con que una empresa del sector industrial cuenta; como resultado se elaboró una tabla que permitió esclarecer los recursos que la compañía habitualmente utiliza para comunicarse con clientes y proveedores, entre ellas se destacan los portales web, redes sociales (Whatsapp, Facebook, Instagram y Twitter) y telefonía móvil, considerándolas aceptables, pero no necesariamente optimas al momento de establecer una comunicación adecuada. Se concluye entonces, que para facilitar la comunicación con clientes y proveedores se hace necesario implementar herramientas encaminadas a brindar ventajas competitivas, y que se encuentren combinadas con los recursos que dispone la organización, para de esta manera mejorar la funcionalidad empresarial.
Keywords: TECNOLOGÍAS DE LA INFORMACIÓN Y COMUNICACIÓN (TICS); HERRAMIENTAS TECNOLÓGICAS; COMUNICACIÓN